2016
DOI: 10.1186/s12917-017-0957-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of a combination therapy of imepitoin with phenobarbital in dogs with refractory idiopathic epilepsy

Abstract: BackgroundImepitoin was tested as a combination treatment with phenobarbital in an open-label mono-centre cohort study in dogs with drug-resistant epilepsy. Diagnosis of idiopathic epilepsy was based on clinical findings, magnetic resonance imaging and cerebrospinal fluid analysis. Three cohorts were treated. In cohort A, dogs not responding to phenobarbital with or without established add-on treatment of potassium bromide or levetiracetam were treated add-on with imepitoin, starting at 10 mg/kg BID, with titr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
1
5
0
1
Order By: Relevance
“…Ataxia, a common AED side effect [30] was mild or not present in the majority of cases, in line with recent objective evidence demonstrating reduced levels in IE patients treated with imepitoin compared to phenobarbitone [31]. A greater number of side effects were seen in dogs treated with imepitoin alongside other AEDs, which is in line with recent studies; for example, when imepitoin was used as an add-on therapy to phenobarbital, or vice versa, the number of side effects increased [32]. In addition, a recent study of imepitoin polytherapy found that 69% of dogs treated with imepitoin and KBr, and 79% of dogs treated with imepitoin and phenobarbital experienced side effects [33].…”
Section: Discussionsupporting
confidence: 75%
“…Ataxia, a common AED side effect [30] was mild or not present in the majority of cases, in line with recent objective evidence demonstrating reduced levels in IE patients treated with imepitoin compared to phenobarbitone [31]. A greater number of side effects were seen in dogs treated with imepitoin alongside other AEDs, which is in line with recent studies; for example, when imepitoin was used as an add-on therapy to phenobarbital, or vice versa, the number of side effects increased [32]. In addition, a recent study of imepitoin polytherapy found that 69% of dogs treated with imepitoin and KBr, and 79% of dogs treated with imepitoin and phenobarbital experienced side effects [33].…”
Section: Discussionsupporting
confidence: 75%
“…In the current study, 11% of the dogs were aggressive and 5% hyperactive after LEV treatment. The incidence of these two behavioral factors is comparable with other AEDs used in veterinary medicine (20,(38)(39)(40)(41)(42)(43)(44). A study in human medicine performed by White et al (14) showed that 38 of the 553 patients were forced to LEV discontinuation due to behavioral side effects.…”
Section: Discussionmentioning
confidence: 75%
“…Reported side effects for phenobarbital are aggression, restlessness and hyperactivity (20,(38)(39)(40). Imepitoin may also cause behavioral changes such as hyperactivity and aggression (41)(42)(43)(44). Moreover, potassium bromide is also reported to cause these two behavioral changes (10).…”
Section: Discussionmentioning
confidence: 99%
“…Imepitoin is only licensed for the treatment of single seizures. Its efficacy for cluster seizures is a matter of ongoing debate (5)(6)(7)(8). Dog owners and veterinarians considered the development of new ASMs among the three most important research topics for the future (9).…”
Section: Introductionmentioning
confidence: 99%